Subsistence economy and land use strategies in the Burdur province (SW Anatolia) from prehistory to the Byzantine period. (2nd May 2017) - De Cupere, B.; Frémondeau, D.; Kaptijn, E.; Marinova, E.; Poblome, J.; Vandam, R.; Van Neer, W.
Abstract: A reconstruction of the ancient subsistence economy and land use strategies is presented here for the province of Burdur, more specifically the area south and southeast of Lake Burdur, in southwestern Turkey. This review is based on the results from archaeozoological (including bone collagen carbon and nitrogen stable isotope analyses) and archaeobotanical analyses available from seven sites, dated to distinct time periods ranging from the Neolithic to the Middle Byzantine period. The data (both published and unpublished) are compiled with information available on settlement development and dynamics, in the study area. Results show changing agrarian and animal husbandry practices for a period of more than 8000 years, ranging between self-sustaining economies to specialised husbandry practices and an intensive agricultural exploitation of the landscape, in relation to human settlement activities.